2016
DOI: 10.5935/0034-7280.20160068
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness in glaucoma. Concepts, results and current perspective

Abstract: Glaucoma is the leading cause of irreversible blindness in Brazil. Its prevalence and incidence tend to increase significantly in the future, mainly due to the population increase and aging. The scarcity of health care resources and the increasing costs in health require a balanced analysis of health interventions and an efficient allocation of resources. The cost-effectiveness and cost-utility studies are important because they allow a comparison between different alternatives in terms of both their costs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…2 Similar to report by Varma et al, 13 this study findings revealed that the financial burden of glaucoma increases as disease severity increases with time. Furthermore, as noted by Guedes et al, 21 since glaucoma is of genetic origin and cannot be prevented, early detection and diagnosis is the most cost-effective way of managing glaucoma and preventing blindness. Consistent with report by Ocansey et al, 5 this study found a statistically significant difference between the cost burden of glaucoma care and wealth status.…”
Section: Discussionmentioning
confidence: 99%
“…2 Similar to report by Varma et al, 13 this study findings revealed that the financial burden of glaucoma increases as disease severity increases with time. Furthermore, as noted by Guedes et al, 21 since glaucoma is of genetic origin and cannot be prevented, early detection and diagnosis is the most cost-effective way of managing glaucoma and preventing blindness. Consistent with report by Ocansey et al, 5 this study found a statistically significant difference between the cost burden of glaucoma care and wealth status.…”
Section: Discussionmentioning
confidence: 99%
“…Os estudos de custo-utilidade são importantes, pois avaliam tanto os custos como a qualidade de vida relacionados a uma determinada doença. (25) Tabela 4. Custos totais, utilidades (ano de vida ajustado pela qualidade) e análise de custo-utilidade.…”
Section: Discussionunclassified
“…The chronic use of hypotensive eye drops is one of the main factors responsible for the high cost of treating glaucoma 42–44 . In a developing country with scarce resources, a treatment that extends the introduction of eye drops for glaucoma can reduce the direct medical costs of the public health system 45 . Unlike the Light trial, which recruited only newly diagnosed patients, we decided to cover our study for patients who had already used the medications, thus observing an effect, in real life, of the reduction of eye drops and, consequently, direct costs to the Brazilian public system.…”
Section: Discussionmentioning
confidence: 99%